ORGANIZING GROUP WORK IN CLASSROOM INSTRUCTION (Web of Teachers: Inderscience Research, 2025)
This paper discusses the organization of small group work in the classroom, including the components of group work during the lesson, planning for group division, adapting the classroom layout accordingly, the preparation stage, and the structure of group work.